Akselerasi Kitab Kuning Dengan Metode Amtsilati Di Pesantren Bustanul Ulum Batu Bintang Pamekasan - Kholili; Mohammad Usman; Kasuwi Saiban; Wahyudi Widodo (Universitas Garut, 2025)
The yellow book is a compulsory study in Islamic boarding schools, while Nahwu and Sharraf science are the initial keys to mastering the yellow book. This study aims to describe the acceleration of yellow book learning through the Amtsilati method at Bustanul Ulum Islamic Boarding School. The Amtsilati method offers a new formulation in accelerating the mastery of nahwu and sharraf. With a qualitative case study approach through interviews, observations, and documentation, the results of the study show that this method is effective through the stages of planning, implementation, and evaluation (oral, written, practical tests, and khatam exams). The novelty of this study lies in proving the effectiveness of Amtsilati as an accelerative model, which practically improves the ability to read books, accelerates the understanding of nahwu-sharraf, and strengthens the readiness of students in Islamic boarding schools.